Management of premature loss of primary first molar case with simple fixed space maintainer - Sherly Horax (DiscoverSys Inc., 2009)
Early loss of primary molars may cause a space problem for the arch development.Several techniques have been used to treat this problem. One of the therapies thatcould be used is space maintainer therapy. This paper will explain the management ofpremature loss of mandible primary first molar by using a simple fixed spacemaintainer combined with molar band and resin composite.